2014
DOI: 10.1111/pcn.12252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insomnia and its clinical correlates in a general population in Turkey

Abstract: Aim The prevalence of insomnia is influenced by environmental factors. This study aimed to investigate the prevalence of insomnia and its sociodemographic and clinical correlates in a general population‐based survey in Turkey. Methods This population‐based study included 4758 subjects among 5021 who participated in the Turkish Adult Population Epidemiology of Sleep Disorders study. Questionnaire items evaluating insomnia were adapted from the International Classification of Sleep Disorders II and the DSM‐IV‐TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
58
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 32 publications
10
58
3
5
Order By: Relevance
“…Dünya çapında yapılan çeşitli çalışmalar, popülasyonun %10-30, bazıları ise %50-60 kadarında insomni olduğunu göstermiştir. Yetişkinlerde, kadınlarda ve eşlik eden fiziksel veya ruhsal hastalığı olanlarda daha yaygındır (59)(60)(61) (62). Toplum Ateroskleroz Riski çalışmasından elde edilen veriler; insomninin, artmış Koroner Kalp hastalığı, miyokard enfarktüsü veya ölüm riski ile ilişkili olduğunu saptamıştır.…”
Section: İnsomniunclassified
“…Dünya çapında yapılan çeşitli çalışmalar, popülasyonun %10-30, bazıları ise %50-60 kadarında insomni olduğunu göstermiştir. Yetişkinlerde, kadınlarda ve eşlik eden fiziksel veya ruhsal hastalığı olanlarda daha yaygındır (59)(60)(61) (62). Toplum Ateroskleroz Riski çalışmasından elde edilen veriler; insomninin, artmış Koroner Kalp hastalığı, miyokard enfarktüsü veya ölüm riski ile ilişkili olduğunu saptamıştır.…”
Section: İnsomniunclassified
“…Benbir et al analyzed a total of 5021 people in their study of the Turkish adult population epidemiology of sleep disorders (TAPES). The authors demonstrated that the incidence of insomnia among the elderly (aged 65 years and older) was 13.9% 28 . Overall, difficulty in falling asleep was reported to be experienced by 15-45% of the elderly, interrupted sleep by 20-65%, waking up exceptionally early by 15-54%,and inability to wake up rested was 10% [29][30] .…”
mentioning
confidence: 99%
“…Insomnia, which is the most common sleep disorder with a prevalence ranging from 3.4% to 19.1%, depending on the diagnostic criteria and population studied, [1][2][3][4] is a significant public health burden. Moreover, a number of recent studies have found a relationship between insomnia and the prevalence of hypertension.…”
Section: Introductionmentioning
confidence: 99%